4-O-galloylalbiflorin inhibits the activity of CYP3A, 2C9, and 2D in human liver microsomes. (3rd August 2021) - Sun, Yu; He, Mengya; Sun, Yanling; Wei, Jianhong
Abstract: The effect of 4-O-galloylalbiflorin on the activity of cytochrome P450 enzymes (CYP450s) is an important factor that may induce drug-drug interaction. The effect of 4-O-galloylalbiflorin on the activity of CYP450s was evaluated in the presence of 0, 2.5, 5, 10, 25, 50, and 100 μM 4-O-galloylalbiflorin in pooled human liver microsomes. The inhibition model and corresponding parameters were assessed b fitting with Lineweaver-Burk plots. The time-dependent study was performed with the incubation time of 0, 5, 10, 15, and 30 min. 4-O-galloylalbiflorin significantly inhibited the activity of CYP3A, 2C9, and 2 D in a concentration-dependent manner with the IC50 values of 8.2, 13, and 11 μM, respectively. The inhibition of CYP3A was found to be non-competitive and time-dependent with the Ki value of 4.0 μM and the KI/Kinact value of 2.2/0.030 (μM·min). The inhibition of CYP2C9 and 2 D was not affected by the incubation time but was found to be competitive with the Ki values of 6.7 and 6.6 μM, respectively. The inhibitory effect of 4-O-galloylalbiflorin on the activity of CYP3A, 2C9, and 2 D implying the potential drug-drug interaction between 4-O-galloylalbiflorin and the drugs metabolized by these CYP450s.